Analysis of Household Food Security in Peatland Areas Palangka Raya City - Abdul Halim; Pratiwi Subianto; Tiur Rosida Simbolon; Miar Miar; Rima Hayati; Suherman Suherman; M Farras Nasrida; Tri Putri Hutabalian; Dimas Prima Rosa (Jurnal Cita Ekonomika, 2025)
This study aims to analyse the socio-economic factors that influence household food security in the peatland area of Palangka Raya City. The study was conducted using a quantitative approach through secondary data processing and multiple linear regression analysis covering variables such as income, food expenditure, food prices, market access, and income diversification. The results show that household food security is still vulnerable, especially among low-income households and those with high food expenditure. Partially, income has a significant positive effect, food expenditure has a significant negative effect, and food prices have a marginal positive effect, while market access and income diversification have no significant effect. The R² value of 0.706 indicates that the model is able to explain the variation in food security well. These findings emphasise the importance of strengthening household economic capacity and stabilising food prices and supply as strategic steps to improve food security in peatland areas, thus contributing significantly to the formulation of regional economic development and food security policies.